An Analysis Of Regional Dialect Usage Toward Students’ Speaking Ability - Miftah Komala Putri (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
This research was conducted on field study of sociolinguistics in ELT by focusing an analysis of regional dialect usage toward students’ speaking ability. Data source from students’ regional dialect usage on an analysis toward students’ speaking ability namely to know about the regional dialect of students’ itself. The aim of this research was obtained the data of research by finding out the process of research and described an analysis of regional dialect toward students’ speaking ability. Meanwhile, the methodology of this research was case study. The researcher collected the technique data by using some instruments such as observation, recording and documentation. The use of technique analysis was using analysis interactive. The sampling of this research was the students in class four at Mega Utama Tunas Bangsa Islamic studies primary school. The process of study research was analyzed by the students and also gave the study guidance that students were to do the instruction given by the researcher, in order to know students’ speaking ability. The result of the research, there were two dialects in the Java language of Banten that were found by the researcher and the cause of students’ regional dialect was that students were more comfortable because the language they speak was the mother tongue. Meanwhile, the conclusion was students should be guided in fun or easy learning of speaking ability in both Indonesia or English lessons so that they became people who are not easily switched to other language cultures and Indonesian culture must be preserved.